Dermatoscopy in polypoid basal-cell carcinoma: a rare histopathological variation - Mariana A. Almeida; Gabriella C. Carmo; Michele R. Feroldi; Gustavo Verardino (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Polypoid basal-cell carcinoma (BCC) is a rare tumor, considered a clinical and histopathological variant of the nodular BCC, presenting broad exophytic or pedunculated base that connects to the surface of the skin and histopathologically displays the neoplastic aggregations restricted to the polypoid zone. We report a clinical case of BCC, with a bibliographical review, highlighting the clinical similarity of such malignant tumor with other benign and malignant tumors of the skin, besides the importance of dermoscopy for the diagnostic aid.